Mapping self-regulated learning research in mathematics education for quality education: A bibliometric analysis (2016–2025) - Nur Fadillah; Kidung Valen Nastiti; Naysa Nafisa Putri; Meiliza Salsabila Putri; Adji W.S. Minadja (CV. SPDFHarmony, 2026)
Background: Although Self-Regulated Learning (SRL) has been extensively studied in mathematics education, existing studies primarily report empirical findings, while the intellectual structure, thematic evolution, and emerging research directions of the field remain insufficiently synthesized. This limitation hinders a comprehensive understanding of research development and future priorities.Aims: This study aims to analyze trends in publications and citations, the most influential authors and journals, co-occurrence patterns of keywords, temporal trends in research topics, and the density of research topics related to SRL in mathematics education to support Quality Education.Methods: A quantitative bibliometric approach was employed using the Dimensions database. Publications published between 2016 and 2025 were retrieved using the keywords